BERENTAK DALAM RITUAL BESALE SUKU BATIN SEMBILAN KABUPATEN BATANGHARI, PROVINSI JAMBI, (KAJIAN ANALISIS TEKS DAN KONTEKS) - Suci Intan Maulia; I Dewa Ayu Sri Utari (Universitas Andalas, 2018)
This research aimed to analyze the existence of a ritual besale typical movement, movement in the besale ritual process is berentak. Berentak motion is a movement running straight forward, backward, around and jumping, the movement continues to be done by Malin Pengasu (shaman) during the process of ritual besale. Besale is from of a magical traditional ceremony, which lives in remote indigenous communities of Suku Batin Sembilan, precisely in Jambi Province forest area. Besale (berasale) means the origin of man, ritual besale involves Malin Pengasu (shaman) and Sidi (good spirits who treat the sick through shaman), to cleanse and cast out the evil spirits that are considered as the source of the disease. Malin Pengasu (shaman) is a person who set all forms of preparation of beterkas up to the ritual besale. The research using the method of qualitative approach text and the context of according Y. Sumandiyo Hadi, which analyze and review the form, techniques, and style the choreography, and analyze the context of based social culture community. The results of research show about how the process of choreography and the emergence of distinctive motion in ritual besale, which in principle socio-cultural society that has been behind the presence of form, technique and style of motion.